"Slightly prepared:" A survey of how archival professionals develop management skills. Issue 1 (3rd April 2021) - Flynn, Kara
Abstract: This study discusses the results of a 2020 survey of 60 archival professionals focused on how archivists and special collections librarians develop their management skills. The study found that although most respondents reported feeling moderately confident about their management skills, most felt that their graduate archival or library education had "slightly prepared" them for the managerial duties of their current position. Rather than learning management skills through their MLIS programs, respondents acquired theses skills largely through professional development opportunities offered by the workplace.